PENDAMPINGAN INOVASI DALAM BUDIDAYA JAMUR: MENGOPTIMALKAN PRODUKSI DAN MENINGKATKAN PENDAPATAN PELAKU UMKM DI DESA LEBAK WANGI KECAMATAN WALANTAKA - Asnawi; Nurhalifah; Sayyidatunnisa; Illahiah, Maddah; Hunayah, Dedeh; Suhartini; Windasari, Sahana Sri; Rumdanah; Julailah; Yayah, Enok (UNIVERSITAS SERAMBI MEKKAH, 2024)
Innovation assistance in mushroom cultivation in Lebak Wangi Village aims to increase the productivity of mushroom farmers. Through the application of appropriate cultivation technology, such as the selection of superior varieties, optimal use of growing media, and effective pest and disease control, it is expected to increase yields and farmers' income. In addition, the assistance also includes business management training to improve the efficiency and competitiveness of local mushroom products. Innovation assistance in mushroom cultivation in Lebak Wangi Village prioritizes the principles of sustainability. Farmers are encouraged to implement environmentally friendly cultivation practices, such as the use of organic fertilizers and good waste management. In addition, the assistance also includes efforts to build strong and independent farmer groups.